Effect of different dietary energy and protein levels on production performance of hy -line W36 layers in Egypt at first stage of production - Alaily, H.A.EL; Fathi, M.M.; EL Aflfi, SH.F.; Elsied, M.M. (2003)
An experiment was conducted to investigate the effect of different dietary energy and protein levels on performance of Hy-Une W36 white layers. One hundred and eighty laying hens at 1Bweeks of age were fed on nine experimental iets containing 3 levels of crude protein (16, 18 and 20%) and 3 levels of metabolizable energy (2750,2850,and 2950kcal ME/kg feed) in a facto rial arrangement design ( 3 protein levels X 3 energy levels).
Includes references.
Summary in Arabic.
1
Keywords: Chickens -- Feeding and feeds; Eggs -- Quality; Energy metabolism; Dietary fats